A novel bottom-up methodology for design and fabrication of three-dimensional braided hybrid composites based on the law of yarn routing and grouping. Issue 9 (May 2023) - Cheng, Yanan; Quan, Zhenzhen; Gu, Qiujin; Yu, Jianyong
A hybrid is an effective means to improve the comprehensive properties of composites. In the current article, by investigating the yarn routing and grouping law in three-dimensional braiding, a novel bottom-up methodology for the design and fabrication of three-dimensional braided hybrid composites is proposed based on the [ m, m ] hybrid unit. Three-dimensional braided hybrid composites with different sizes of hybrid unit were prepared and drop-hammer based impact tests were conducted to study the composites' dynamic mechanical performances. It was found that the three-dimensional braided hybrid composites based on the bottom-up methodology present much better structural integrity and toughness than conventional ply-stacked hybrid counterparts and significant dependence of mechanical performances on the size of hybrid unit. We found that the smaller the size of hybrid unit, the better the mechanical performance. The results demonstrated the feasibility and effectiveness of the proposed bottom-up methodology and could enable the design and fabrication of three-dimensional braided preforms and composites with certain well designed structures and functions.